Efficacy Test of Lemon Juice (Citrus Limon) on Acne to Inhibit the Growth of Propionibacterium Acnes 2025 - Nurhidayah Nurhidayah; Lisdawaty Siregar; Ade Arhamni (International Journal Labs, 2025)
Acne (Acne Vulgaris) has now developed into a very annoying skin disease that can even leave scars (acne scar). Records from Indonesian cosmetic dermatology continue to increase, namely 60% of acne vulgaris sufferers in 2006, 80% in 2007 and 90% in 2009. Propionibecterium acnes is one of the pathogenic bacteria that plays a role in the onset of acne vulgaris and inflammatory diseases. Lemon water (Citrus limon) is known to contain limonene and quercetin, which are able to act as anti-inflammatory and inhibit the growth of P.acnes. The purpose of this study is to determine the effectiveness of adding lemon water extract to face toner preparations to inhibit the growth of P. acnes. The extraction method used was maceration using ethanol and methanol solvents and was carried out for 24 hours, 48 hours and 72 hours, in this study using 5 days (120 hours). The concentration of extracts used is 20%, 40%, 60%, 80% and 100%. The bacterial test method used is the diffusion of paper disk or nutrient agar with observations carried out every 12 hours. The results of the one-way-ANOVA statistical test showed no significant difference in the change in the concentration of lemon peel extract in the face toner preparation to the diameter of the P. acnes growth inhibition zone (p > 0.05). Based on research conducted for 120 hours, maceration has the highest quercetin content with methanol solvent, but the best antibacterial activity is face toner with lemon water extract content with ethanol solvent. The addition of 1% lemon water extract already had bacterial activity, but P. acnes was able to resist faster compared to higher concentrations.